Growth Percentage And Length Of Mucuna Bracteata Tendles With The Provision Of Local Microorganisms (Mol) From Banana Corn - Tanjung, Agung Rafiul Naldi; Ginting, Chelvin Van Roy; Sulastri, Yustina Sri; Sihaloho, Martha Adiwaty; Sitinjak, Rama Riana; Pratomo, Bayu (Agroprimatech, 2025)
Mucuna bracteata plants can be propagated in two ways: generatively and vegetatively. Vegetative propagation is done through cuttings, while generative propagation uses seeds. In 1999, Mucuna bracteata found it very difficult to produce flowers, fruits, and seeds. Due to this difficulty, propagation can be done through cuttings. This study uses a Non-Factorial Randomized Block Design (RBD) with 4 Treatments (P) and 6 Replications (U). The concentration of watering consists of 4 levels: P0 (0 ml), P1 (50 ml), P2 (150 ml), and P3 (250 ml). Meanwhile, the soaking duration also consists of 4 levels: P0 (0 minutes), P1 (5 minutes), P2 (10 minutes), and P3 (15 minutes). The results of the study showed that the interaction between the concentration of watering with MOL (Microorganism Local) from banana stems and the soaking duration did not have a significant effect on all parameters. Various concentrations of watering with MOL from banana stems and soaking duration significantly affected the growth of Mucuna bracteata. Although statistically, it did not show a significant effect, several treatment combinations could be observed, such as U6P3, which showed the highest root weight (15.44 grams). Then, the vine length was 117.1 cm, the number of leaves was 20, and the number of nodules was 11. As the highest values from P3, this shows the highest concentration of watering and soaking duration with MOL from banana stems. Thus, this effort can reduce agricultural waste and pathogens.